Early postoperative calcitonin-to-preoperative calcitonin ratio as a predictive marker for structural recurrence in sporadic medullary thyroid cancer: A retrospective study - Jiao, Zan; Wu, Tong; Jiang, Mingjie; Jiang, Shuxian; Jiang, Ke; Peng, Jin; Luo, Guangfeng; Yu, Yongchao; Chen, Weichao; Yang, Ankui (Frontiers in Endocrinology, 2022)
Background: Calcitonin measurement is widely used in the diagnosis, prognosis, and follow-up of patients with medullary thyroid carcinoma (MTC). The prognostic value of postoperative calcitonin-to-preoperative calcitonin ratio (CR), reflecting the change in Ctn level of response to initial treatment, remains uncertain in long-term disease outcomes. The aims of this study were to determine the CR cut-off value for predicting structural recurrence and evaluate its prognostic value. Methods: Medical records of patients treated for MTC in Sun Yat-sen University Cancer Center (SYSUCC) between 2000 and 2022 were retrospectively reviewed. CR is defined as the ratio of postoperative Ctn level on the day of discharge divided by preoperative Ctn level. Receiver operating characteristic (ROC) analysis was used to determine the optional cut-off value. We used the Kaplan-Meier approach and Multivariable Cox regression analysis to investigate the impact of CR on recurrence-free survival (RFS) and a nomogram based on CR was constructed. Results: A total of 112 sporadic MTC were included in the study. The optional cut-off value of CR that predicted disease recurrence was 0.125. Patients with CR≥0.125 showed significantly worse RFS than patients with CR <0.125, respectively (3-years RFS rate of 63.1 vs. 94.7%, 5-years RFS rate of 50.7 vs. 90.3%, P < 0.001). In the multivariate analysis, CR was the strongest independent predictor of structural recurrence (HR: 5.050, 95% CI: 2.247–11.349, P <0.001). Tumor size (HR: 1.321, 95% CI: 1.010–1.726, P =0.042), multifocality (HR: 2.258, 95% CI: 1.008–5.058, P =0.048) and metastasized lymph nodes (HR: 3.793, 95% CI: 1.617–8.897, P <0.001) were also independent predictors of structural recurrence. The uncorrected concordance index (c-index) of the nomogram was 0.827 (95% CI, 0.729-0.925) for RFS, and bias-corrected c-index were similar. Moreover, ROC and DCA analysis demonstrated better accuracy and discrimination of 3- and 5-year RFS with CR-based nomogram compared to TNM stage. Conclusions: We demonstrate that CR is a strong prognostic marker to predict structural recurrence in patients with sporadic MTC. The nomogram incorporating CR provided useful prediction of RFS for patients with sporadic MTC to provide personalized treatment.